PENGARUH KUALITAS PELAYANAN, HARGA DAN LOKASI TERHADAP KEPUASAN KONSUMEN PADA HOTEL ILOS BANDUNG - Erick Ivan Gian; Ida Bagus Alit Ksama Putra; R Maman R Maman Nurochman; Priatna Kesumah; Risna Haryati; Putri Dwi Novrina; Hanny Arifin (Jurnal Ilmiah Magister Ilmu Administrasi, 2023)
This study aims to examine the effect of: (1) service quality, price and location on consumer satisfaction, (2) service quality on consumer satisfaction, (3) price on consumer satisfaction, (4) location on consumer satisfaction. The research design used in this research is causal quantitative research. In this study, the research subjects were consumer who visited Hotel Ilos Bandung and the objects of research were service quality, price, location and consumer satisfaction. The population taken in this study were all consumer who visited the Ilos Bandung Hotel which amounts to 35 people. Data were collected by interviews, document recording and questionnaire methods, then analyzed by multiple regression analysis. The results showed that: (1) service quality, price and location had a significant effect on consumer satisfaction, (2) service quality had a significant effect on consumer satisfaction, (3) price had a significant effect on consumer satisfaction, (4) location had a significant effect on consumer satisfaction.